2007
DOI: 10.1212/01.wnl.0000268485.93349.58
|View full text |Cite
|
Sign up to set email alerts
|

Hospital volume and stroke outcome

Abstract: High annual hospital volume was consistently associated with lower stroke mortality. Our study encourages further research to determine whether this is due to differences in case mix, more organized care in high-volume facilities, or differences in the performance or in the processes of care among facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
100
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(113 citation statements)
references
References 46 publications
9
100
0
4
Order By: Relevance
“…This is important, because the pattern of stroke is rapidly changing in Asia with urbanisation, causing an increase in rates of ischemic stroke, and a need to provide pathways and protocols similar to those reported in western countries. [15] MIC hospitals were predominantly larger with high patient-flow, and this 'volume-outcome relationship' has been shown to be an important predictor of short-term mortality in some, [16] but not all, [17] stroke studies. However, participating HIC hospitals may have adopted a twotiered (or 'hub-and-spoke') model of stroke care in which a central 'comprehensive stroke centre' serves a number of smaller hospitals working as 'primary stroke centres' for thrombolysis of AIS patients, using protocols for transfer to larger hospitals for interventional therapies and telemedicine assistance.…”
Section: -Discussionmentioning
confidence: 99%
“…This is important, because the pattern of stroke is rapidly changing in Asia with urbanisation, causing an increase in rates of ischemic stroke, and a need to provide pathways and protocols similar to those reported in western countries. [15] MIC hospitals were predominantly larger with high patient-flow, and this 'volume-outcome relationship' has been shown to be an important predictor of short-term mortality in some, [16] but not all, [17] stroke studies. However, participating HIC hospitals may have adopted a twotiered (or 'hub-and-spoke') model of stroke care in which a central 'comprehensive stroke centre' serves a number of smaller hospitals working as 'primary stroke centres' for thrombolysis of AIS patients, using protocols for transfer to larger hospitals for interventional therapies and telemedicine assistance.…”
Section: -Discussionmentioning
confidence: 99%
“…Hospital volume has been linked to stroke mortality. 17 It needs to be further investigated whether the PSCs certified only by the state has the same outcome when compared with the PSCs certified by JC.…”
Section: Discussionmentioning
confidence: 99%
“…Even if such an infrastructure were created, there would not be sufficient numbers of patients to ensure adequate treatment volumes that have repeatedly been shown to correlate with overall quality of care. [29][30][31][32][33][34] The importance of adequate patient volume to overall outcome has been well documented both in neurovascular care, such as in the treatment of cerebral aneurysms 31,35 and in carotid stenosis, 36,37 as well as in similar emergent disease processes, such as percutaneous coronary intervention 38,39 Grigoryan et al 28 performed a nationwide inpatient sample database analysis of participating hospitals and evaluated the number of stroke-related procedures performed at each institution. The results of the analysis indicated that few hospitals in the United States were meeting the procedure volume necessary, based on previous trial experience requirements for operator inclusion (such as those for the Asymptomatic Carotid Atherosclerosis Study or the International Subarachnoid Aneurysm Trial), to ensure satisfactory operator experience.…”
Section: Stroke Centers: the More The Better?mentioning
confidence: 99%
“…[29][30][31] Similarly, there is evidence to suggest that higher volume stroke centers are associated with higher rates of good outcomes compared with lower volume centers. [32][33][34] These studies provide a convincing argument that appropriately equipped centers with physicians and staff who routinely treat stroke have better outcomes than centers that treat only small numbers of such patients.…”
Section: Stroke Centers: the More The Better?mentioning
confidence: 99%